Impact of age-related neuroglial cell responses on hippocampal deterioration - Ojo, Joseph O.; Rezaie, Payam; Gabbott, Paul L.; Stewart, Michael G. (Frontiers in Aging Neuroscience, 2015)
Aging is one of the greatest risk factors for the development of sporadic age-related neurodegenerative diseases and neuroinflammation is a common feature of this disease phenotype. In the immunoprivileged brain, neuroglial cells, which mediate neuroinflammatory responses, are influenced by the physiological factors in the microenvironment of the central nervous system (CNS). These physiological factors include but are not limited to cell-to-cell communication involving cell adhesion molecules, neuronal electrical activity and neurotransmitter and neuromodulator action. However, despite this dynamic control of neuroglial activity, in the healthy aged brain there is an alteration in the underlying neuroinflammatory response notably seen in the hippocampus, typified by astrocyte/microglia activation and increased pro-inflammatory cytokine production and signalling. Normally, these changes occur without any concurrent pathology, however, they can correlate with deteriorations in hippocampal or cognitive function. In this review we examine two important phenomenons, firstly the relationship between age-related brain deterioration (focusing on hippocampal function) and underlying neuroglial response(s), and secondly how the latter affects molecular and cellular processes within the hippocampus that makes it vulnerable to age-related cognitive decline.